The Evolution of Neurosurgery Throughout the Ages: From Trepanations in Prehistory to The Robotic Era - Souza, Felipe dos Santos; Silva, Rhuann Pontes dos Santos; Junior, Luiz Severo Bem; Azevedo Filho, Hildo Rocha Cirne de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Throughout the historical course, the emergence of neurosurgery invariably involved the narrative about different eras, marked by relevant discoveries in the field of medical science. From prehistoric mystical and therapeutic reports to the Robotic Era in the 21st century, there were changes that contributed to current neurosurgery. Thus, this study will analyze articles and studies that describe the history of neurosurgery and demonstrate the main advances in the field of science.Materials and methods This is a narrative review of scientific literature, carried out by searching the following databases: Scientific Electronic Library Online (SCIELO), Online System for Searching and Analyzing Medical Literature (MEDLINE), Latin American Literature and Caribbean in Health Sciences (LILACS), and Public Medical Literature Analysis and Retrieval System Online (PubMed).The following descriptors were used: History of neurosurgery and Neuroanatomy, together with the Boolean operator “AND”. In addition, the descriptors HistoryofNeurosurgery and Robotics were used between the Boolean operator “AND”. In this sense, in order to establish a linearity of the narrative presented, the evolution of neurosurgery in five eras was didactically separated.Conclusion Neurosurgery, throughout history, has undergone several transformations. There was a series of events that made neurosurgery one of the most evolutionary and progressive sciences. This is because technology combined with scientific knowledge was, in fact, what made it possible to get where we are. In this sense, the studied ages allow the comprehension of a history that needs to be understood and valued by all students of the neurological and neurosurgical sciences.
Keywords: neuroanatomy; history; neurosurgery; robotic surgical procedures